2022
DOI: 10.1111/sum.12860
|View full text |Cite
|
Sign up to set email alerts
|

The difference in soil organic carbon distribution between natural and planted forests: A case study on stony soils mountainous area in the Upper Min River Arid Valley, China

Abstract: Few studies have been conducted on the factors and distribution of soil organic carbon (SOC) in plantation forests in arid mountainous regions, especially in orchards. We aimed to unravel the SOC distribution among land‐use types and the effects of altitude gradients and rock fragment content (RFC) on SOC accumulation and sequestration in the Upper Min River Arid Valley, China. The differences in SOC distribution among land‐use types were quantified. The correlation analysis of SOC with various factors, such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 120 publications
0
1
0
Order By: Relevance
“…So, what is the range of the appropriate amount of soil gravel? Wang et al [48] found the highest SOC stocks under 40-50% gravel cover in the cold and arid desert of the Northwest Tibetan Plateau; Han et al [49] found that rock fragment contents (5-55%) in orchards positively correlated with SOC contents in dry valleys in western Sichuan, China. Farmers in this region varied widely in their understanding of the appropriate range of soil gravels (soil in some orchards contained 36.8% gravel, while others contained only 11.8%; see Table 1).…”
Section: Effects Of Management Practices On Soc Sequestration In Orch...mentioning
confidence: 99%
“…So, what is the range of the appropriate amount of soil gravel? Wang et al [48] found the highest SOC stocks under 40-50% gravel cover in the cold and arid desert of the Northwest Tibetan Plateau; Han et al [49] found that rock fragment contents (5-55%) in orchards positively correlated with SOC contents in dry valleys in western Sichuan, China. Farmers in this region varied widely in their understanding of the appropriate range of soil gravels (soil in some orchards contained 36.8% gravel, while others contained only 11.8%; see Table 1).…”
Section: Effects Of Management Practices On Soc Sequestration In Orch...mentioning
confidence: 99%